2012
DOI: 10.1186/1556-276x-7-297
|View full text |Cite
|
Sign up to set email alerts
|

Non-solvolytic synthesis of aqueous soluble TiO2 nanoparticles and real-time dynamic measurements of the nanoparticle formation

Abstract: Highly aqueously dispersible (soluble) TiO2 nanoparticles are usually synthesized by a solution-based sol–gel (solvolysis/condensation) process, and no direct precipitation of titania has been reported. This paper proposes a new approach to synthesize stable TiO2 nanoparticles by a non-solvolytic method - direct liquid phase precipitation at room temperature. Ligand-capped TiO2 nanoparticles are more readily solubilized compared to uncapped TiO2 nanoparticles, and these capped materials show distinct optical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…This peak was around 240 nm. This result is in agreeement with that of Chen et al [20], which indicate the absorbance intensity of GalA-TiO2 NPs dispersion in the UV region at <300 nm. Figure 4, it is concluded that 100 µl of saliva is the best volume for measuring the ALP activity according to the conditions of experiments.…”
Section: Introductionsupporting
confidence: 93%
“…This peak was around 240 nm. This result is in agreeement with that of Chen et al [20], which indicate the absorbance intensity of GalA-TiO2 NPs dispersion in the UV region at <300 nm. Figure 4, it is concluded that 100 µl of saliva is the best volume for measuring the ALP activity according to the conditions of experiments.…”
Section: Introductionsupporting
confidence: 93%
“…Whilst the metal oxide phase precipitates as small NPs the by-product NaCl remains dissolved in the alcoholic solution. The process can be used for a variety of metal oxide products such as Cu2O, WO3 or even ternary phases such as CoFe2O3, 199,200 with additives (e.g. alkylamines and oleic acid) enabling improved monodispersity of the NPs.…”
Section: Hydrolysis Routes To Metal Oxide Nanoparticlesmentioning
confidence: 99%
“…Amongst the reported processes, the most common are the hydrothermal and solvothermal methods, in which the precursor is precipitated in water, organic solvents or ionic liquids, and the precipitate is crystallised by a thermal treatment. 23,24 The solvothermal route is one of the most extensively applied methods for the synthesis of NPs. Buonsanti et al developed a novel method to prepare unique branched-shaped nanocrystals of TiO 2 NPs, by mixing titanium carboxylate complexes and mixtures of oleic acid and oleyl amine at 240-320 °C.…”
Section: Introductionmentioning
confidence: 99%